الخروج عن القياس في أبنية مصادر الثلاثيّ المزيد - العطا, أمل (جامعة الوادي - University of Eloued, 2020)
ملخّص: يسعى البحث إلى معرفة أبنية مصادر الثلاثي المزيد المخالفة للقياس، ومسوّغ مجيئها، وهل دلّت على معانٍ زائدة مخالفة لمعنى القياسيّ منها، أو المعنى واحد من باب التوسّع في الثراء اللفظيّ؟ وركّز على أبنية المصادر غير القياسيّة التي ذُكرت مع القياسيّة وتعدّدت معها، وتتبّعها في معجم تاج العروس للزبيديّ (ت 1205ه). واشتمل البحث على محورين، المحور الأوّل: الخروج عن قياس أبنية مصادر الثلاثيّ المزيد بحرف، وتناول الخروج عن قياس أبنية (إفْعَال)، و(تَفْعِيْل)، و(مُفَاعَلَة)، والمحور الثاني: الخروج عن قياس أبنية مصادر الثلاثيّ المزيد بحرفين، وتناول الخروج عن قياس أبنية (تَفَعُّل)، و(تَفَاعُل)، (وافْتِعَال)، و(انْفِعَال)، ولم يقف البحث على الخروج عن قياس بناء (اِفْعِلَال)، كما لم يقف على الخروج عن قياس أبنية مصادر الثلاثيّ المزيد بثلاثة أحرف. Abstract: This study aims to explore the structure of verbal nouns derived from augmented triliteral root verbs that deviate from the standard pattern, the reasons for their existence, and whether they denote additional meanings different from the standard one, or have the same meanings but exist merely for the sake of linguistic variety. The study concentrates on the structures of non-standard verbal nouns that are mentioned along with the standard form, but in addition to it. These are looked up in Al-Zabidi's dictionary ‘taajul- ξaruus min jawaahiril-qαmuus( )(1205 A.H.). The research examines two topics: (i) deviation from the standard pattern while structuring the verbal nouns for triliteral root verbs augmented with a single letter; where the researcher deals with deviation from the standard patterns for ?ifξaal, tafξiil and mufaaξalah, and (ii) deviation from the standard patterns while structuring verbal nouns for triliteral root verbs augmented with two letters; where the researcher deals with deviation from the standard patterns for tafaξ-ξul, tafaaξul, ?iftiξaal and ?infiξaal . The research does not examine deviations from pattern ifξilaal, nor deviations from the pattern for verbal nouns augmented with three additional letters. Key Words: deviation, empiricism, standard pattern, structures, root verbs, triliteral verbs, augmented verbs.
مقال
Keywords: الخروج، السماع، القياس، الأبنية، المصادر، الثلاثيّ، المزيد